2007
DOI: 10.1111/j.1095-8649.2007.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet partitioning in sympatric Atlantic salmon and brown trout in streams with contrasting riparian vegetation

Abstract: Prey intake by Atlantic salmon Salmo salar and brown trout Salmo trutta was measured across different riparian vegetation types: grassland, open canopy deciduous and closed canopy deciduous, in upland streams in County Mayo, Western Ireland. Fishes were collected by electrofishing while invertebrates were sampled from the benthos using a Surber sampler and drifting invertebrates collected in drift traps. Aquatic invertebrates dominated prey numbers in the diets of 0þ year Atlantic salmon and brown trout and 1þ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 71 publications
1
59
0
Order By: Relevance
“…Noteworthy, our findings can exemplify the interface between terrestrial and aquatic ecosystems through the feeding of top predators in riverine food webs (here brown trout). As noted in the Introduction, other workers have found that terrestrial invertebrates may enhance fish production, food resource partitioning among competing species and stream benthic community (Edwards and Huryn, 1995;Nakano et al 1999a;Dineen et al, 2007). That said, planning of restoration works or land-use practices on river basins should take into account the input of terrestrial invertebrates from the riparian canopy as a key factor for food supply of streamdwelling salmonids species, as well as other advantages in ecosystem processes such as resource partitioning or trophic cascades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, our findings can exemplify the interface between terrestrial and aquatic ecosystems through the feeding of top predators in riverine food webs (here brown trout). As noted in the Introduction, other workers have found that terrestrial invertebrates may enhance fish production, food resource partitioning among competing species and stream benthic community (Edwards and Huryn, 1995;Nakano et al 1999a;Dineen et al, 2007). That said, planning of restoration works or land-use practices on river basins should take into account the input of terrestrial invertebrates from the riparian canopy as a key factor for food supply of streamdwelling salmonids species, as well as other advantages in ecosystem processes such as resource partitioning or trophic cascades.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, inputs of terrestrial invertebrates from riparian canopy cover may represent an important food resource for stream-dwelling fish species (Kawaguchi and Nakano, 2001;Utz and Hartman, 2007;Syrjänen et al, 2011). Therefore, the importance of terrestrial invertebrates in riverine systems is unquestionable, such importance has been identified in different ways; that is, in terms of energy subsidy for fish species (Edwards and Huryn, 1996;Nakano et al, 1999b;Utz and Hartman, 2007), annual fish production (Edwards and Huryn, 1995), food resource partitioning between sympatric fish species (Dineen et al, 2007; or ecosystem functioning (Nakano et al, 1999c). That said, it should be kept in mind that the terrestrial invertebrate input to the riverine systems greatly depends on riparian canopy cover (Edwards and Huryn, 1996;Kawaguchi and Nakano, 2001;Ryan and KellyQuinn, 2015), but this allochthonous prey supply occurs primarily during summer, when aquatic invertebrate biomass is usually low (Nakano and Murakami, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial invertebrates may largely cover the energy intake of streamdwelling salmonids in summer (Sánchez-Hernández and Cobo, 2016). This reduces interspecific competitive interactions for benthic invertebrates through resource partitioning (Dineen et al, 2007), and becomes an important mechanism promoting the coexistence of related fish species (Miyasaka et al, 2003). Therefore, it is possible that the observed shift in brook trout diet from our study resulted from competitive interactions with brown trout.…”
Section: Discussionmentioning
confidence: 90%
“…An important mechanism allowing the species to reduce competition is food resource partitioning, including both spatial and temporal differentiation and changes in feeding habits (Pianka 1969;Schoener, 1974). Indeed, it has been formerly shown that the interaction between related salmonid species magnifies the differences in the use of habitat or food resources (Blanchet et al, 2007;Dineen et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation